The local development of a district in the Puno region through rural tourism (Gestionar: revista de empresa y gobierno, 2023)
Local development is delimited by a coordinated process supported by evidence and experiences, implying the need for technical guidance to efficiently utilize available resources. It is emphasized that local initiatives have identified tourism activity in rural settings as an emerging opportunity. This study aimed to determine the relationship between local development and rural tourism management in the Capachica district. The research was conducted using a quantitative correlational approach, adopting a non-experimental design. The probabilistic sample included 304 residents of the Capachica district, who were administered two questionnaires. The results indicate a direct relationship, ranging from weak to moderate (0.340). In conclusion, limitations in local development and rural tourism management are evident, highlighting the imperative need to enhance and optimize tourism management to achieve community growth and position the Capachica district as a hub for rural tourism activity in the Puno region.
Keywords: local development; management; rural tourism; sustainability; tourism resources